The reality of the right to play and its importance in the kindergarten from the viewpoint of the parameters "A field stady in Lattakia" - Terko, Mohammad; Nasser, Rasha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to identify the reality of the right to play in the kindergarten of Lattakia, and its importance from the viewpoint of the parameters, it aims also to identify the differences in their views about the reality of the right to play in the kindergarten of Lattakia according to (kindergarten location, scientific and educational qualification, years of experience, training courses). This research adopts the descriptive approach, and it uses a questionnaire that consists of (40) phrases as a tool to collect data from the sample of the research which consists of (272) teachers in the kindergarten of Lattakia (2016- 2017). Results have shown that: 1- The right to play in the kindergarten of Lattakia was present to an intermediate level, and its importance was present to a high level 2- There are no differences among sample members point of view regarding the level of the right to play in the kindergarten of Lattakia according to (years of experience). 3- There are differences according to kindergarten location in favor of the city, according to scientific and educational qualification in favor of the university degree educational campaign ,and according to training courses in favor of teachers who followed training courses.